Systematic literature review of the role of libraries in increasing data privacy awareness in artificial intelligence based library services - Suci Yanti Ramadhan; Wan Ainol Mursyida binti Ahmad Tarmizi; Angga Hadiapurwa; Lutfi Khoerunnisa; Yayu Wulandari (Library and Archive, Universitas Gadjah Mada, 2026)
Introduction. The transformation of library services driven by the development of artificial intelligence (AI) has raised serious challenges related to the protection of user privacy and data security. This study aims to systematically analyze the role of libraries in enhancing data privacy awareness. Research Methods. This study employs a Systematic Literature Review (SLR) method. The literature search was conducted using the Google Scholar, ScienceDirect, Springer, and Taylor & Francis databases, covering publications from 2022 to 2025. Data Analysis. The selection process based on predefined inclusion and exclusion criteria resulted in 20 articles, which were analyzed using a descriptive qualitative approach. Results. AI is widely used in library services, while libraries play a strategic role in promoting data privacy awareness through policies, security, and ethics-based digital literacy. Conclusion. The findings confirm that libraries are not only information providers but also key actors in promoting data privacy awareness through policy development, user education, and ethical governance of AI-based services.